Social Determinants in Association with Postpartum Blues during the Transition Period of COVID-19 Pandemic - Mujab, Salwa Tsabitah Althaf; Theresa, Ria Maria; Saleh, Arman Yurisaldi; Lardo, Soroy (Journal of Maternal and Child Health, 2023)
Background: The COVID-19 pandemic has considerably impacted individuals' lives, extensively from mental and socioeconomic aspects, that requires someone to adapt. For postpartum mothers who also need to go through the maternal psychological adaptation phase, the pandemic could impose overwhelming emotional tension on them, increasing the risk of experiencing postpartum blues. This study aims to analyze the relationship between social factors that are affected during a pandemic with the incidence of postpartum blues on screening test results during the transition period of the COVID-19 pandemic in Banyumanik, Semarang. Subjects and Method: This was a cross-sectional study conducted in Banyumanik, Semarang, from November to December 2022. 39 subjects were selected using a consecutive sampling technique. The dependent variable is postpartum blues. The independent variables include marital status, employment status of the mother, employment status of the spouse, and family income level. The study instrument was EPDS questionnaire. The data were analyzed used Chi-square. Results: Out of 39 subjects, 13 (33.3%) were experiencing postpartum blues, and 26 (66.7%) were not experiencing it. Mother’s employment status associated with postpartum blues. Mothers who unemployed have a risk of experiencing postpartum blues 1.65 times compared to employed, but these were not statistically significant (OR= 1.65; 95% CI= 0.40 to 6.77; p= 0.727). Family income level associated with postpartum blues. Mothers with low to moderate family income reduced postpartum blues by 0.73 times compared to mothers with high income levels, but these were not statistically significant (OR= 0.73; 95%CI= 0.19 to 2.80; p= 0.908). Meanwhile, marital status and spouse employment status were not related to the incidence of postpartum blues. Conclusion: Mother’s employment status and family income status associated with postpartum blues. Meanwhile, marital status and spouse employment status were not related to the incidence of postpartum blues. Keywords: social factors, postpartum blues, screening test results, COVID-19 pandemic. Correspondence: Salwa Tsabitah Althaf Mujab. Medical Bachelor Program, Faculty of Medicine, UPN Veteran Jakarta, Indonesia. Jl. Rumah Sakit Fatmawati, Pondok Labu, Jakarta Selatan, DKI Jakarta 12450. Email: salwatsabitaham@upnvj.ac.id. Mobile: +628122608388.